Optimization and application of quantitative magnetic resonance imaging methods to analyze brain perfusion and function - Paschoal, André Monteiro (2020)
The human brain consists of a very complex and specialized organ and is responsible for coordinating the execution of several functions performed by the subjects. The brain tissue must be continuously supplied with oxygen and all the nutrients necessary to provide the required energy to keep all these mechanisms regulated in a normal condition since the brain is not capable of storing energy. The neurovascular system is crucial to keep the delivery of nutrients constant, though it implies a complex mechanism of auto-regulation. Deregulation of this essential mechanism may impair the delivery of nutrients according to the demand for energy, which may lead to various brain disorders. Magnetic resonance imaging (MRI) is a potent imaging tool that allows the analysis of several characteristics related to brain structure, function, perfusion, water diffusion, and others. These characteristics can be assessed exploiting different possible contrast mechanisms. Arterial Spin Labeling (ASL) and Intravoxel Incoherent Motion (IVIM) are two noninvasive and quantitative methods based on blood perfusion and water diffusion, respectively, which enable the quantification of cerebral blood flow (CBF) and water diffusion coefficient in brain tissue. Moreover, due to the neurovascular coupling, the analysis of the temporal fluctuations in blood perfusion at different anatomical brain regions allows the study of brain functions, which is called functional MRI (fMRI) and consists of a widely used imaging modality to assess brain integrity. In this study, we worked on the interface between the development of image acquisition and analysis methods, and their application in both healthy subjects and patients. Regarding acquisition methods, we worked on the optimization of the 3D Gradient and Spin Echo (GRASE) readout and the effect of flow compensated gradients in ASL images. For IVIM, we evaluated the effect of different acquisition parameters in the analysis model to optimize the analysis for neurological and neurovascular patients. Finally, we evaluated the capability of ASL to study brain functions in a resting-state condition and while performing different actions, such as motor and language tasks. We started with a simple and robust motor task to validate our method and then applied it to study a more complex function (language). We developed and implemented a novel dual-echo readout for ASL protocol to improve quantitative assessment of the CBF and the blood oxygen level-dependent (BOLD) signals. The main findings of this thesis include the better delineation of the arterial signal when using segmented 3D GRASE and flow compensation gradients; the demonstration of the feasibility of ASL with dual-echo readout in a simultaneous accurate quantification of CBF and measurement of BOLD signal for functional analysis; the investigation of the physiological basis for brain functional reorganization and better spatial localization of brain activation of a cognitive task through dual-echo ASL; a description of the start-of-the-art use of IVIM for neurological and neurovascular diseases; an analysis of the impact of IVIM acquisition and analysis parameters to better fit the IVIM measurements, and a pilot study of IVIM applied in patients with brain glioma as a model of the blood-brain barrier disruption.